Strategic analysis of influence peddling - Mukul Majumdar; Seung Han Yoo (Cornell University, Center for Analytical Economics (CAE), 2011)
This paper analyzes Influence Peddling with interaction between human capital transfer and collusion-building aspects in a model, in which each government official regulates multiple firms simultaneously. We show that (i) there exists an optimal division rule for collusion between a sequence of qualified regulators and a firm; (ii) as the regulators increasingly benefit from the collusion, they strictly decrease regulation rates for the firm under collusion while strictly increasing regulation rates for a firm not under collusion; and (iii) post-government-employment restrictions are not effective policies, and an alternative policy can be suggested.
Keywords: D73; H83; L51; 330; revolving doors; signaling games; repeated games